Molybdenum-sulfur double-doped cobalt metal organic framework and preparation method and application thereof
CO9S8 is formed by mixing sulfur element on the cobalt metal organic framework (CO-MOF), and the CO6MOO12 cover layer is formed with the reaction with molybdenum. Improve the catalytic performance and stability of electrolyte anode oxygen.
Patent Information
- Application Number
- CN202411475720.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, the multi-electron transfer step involved in the oxygen precipitation reaction (OER) at the electrolytic water anode has a high theoretical potential and slow kinetics, and the precious metal catalyst reserves are scarce and expensive; at the same time, the active material cannot be used on the foam nickel surface. Even distribution leads to low catalytic performance.
Using molybdenum-sulfur double-doped cobalt metal-organic framework (Mo/S-Co-MOF), S element is doped on the high specific surface area MOF material to form Co9S8, and reacts with Mo element through hydrothermal method to form Co6MoO12 coating layer to build a core-shell structure to improve stability and catalytic performance.
In the 1M KOH solution, when the current density is 10mA · CM-2, the overpower is 255mv, the TAFEL slope is 89mv · DEC-1, and the current retention rate of 87-89%is maintained after the 48H cycle test, which is significant, which is significant, which is significant. Improve the stability and electrochemical properties of catalysts.
Smart Images

Figure CN119331262A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy water electrolysis catalysis, and in particular to a molybdenum-sulfur dual-doped cobalt metal organic framework and a preparation method and application thereof. Background Art
[0002] Water electrolysis hydrogen production technology usually refers to the process of decomposing water into hydrogen and oxygen through discharge at the anode and cathode. Among them, the main bottleneck faced by alkaline water electrolysis hydrogen production technology lies in the high theoretical potential and slow kinetics of the multi-electron transfer steps involved in the oxygen evolution reaction (OER) at the anode end of water electrolysis. The current solution is to improve the catalytic performance based on catalysts made of precious metal materials such as platinum, iridium, and ruthenium, which have good conductivity and high catalytic activity. However, such precious metal materials inevitably have the problem of scarce reserves and high prices.
[0003] Using non-precious metals as hydrogen evolution catalysts, for example, existing literature 1 (Zhong-Yin Zhao, Fei-Long Li, Qi Shao, et al. [J], Advance Materials, 2019, 1900372.) synthesized a cobalt-modified MoS2 hybrid catalyst grown on nickel foam by a simple solvothermal method, which showed good hydrogen evolution performance at 10 mA cm -2 The overpotential is 294mV at a current density of . This technical solution successfully improves the conductivity and thus the catalytic performance by introducing MoS2 as an active substance. However, the problem with this technical solution is that due to the smooth surface of nickel foam, the active material cannot be evenly distributed when loaded, and agglomerates, which prevents a large number of active sites from participating in the reaction, thereby affecting the catalytic performance of the material.
[0004] In order to solve the contact problem between the active material and the nickel foam, a high specific surface area material can be first loaded on the nickel foam, and then the active substance can be loaded through the high specific surface area material, that is, a transition layer is introduced between the active material and the nickel foam, thereby improving the catalytic performance.
[0005] For example, existing literature 2 (Huizhu Xu, Ke Ye, Kai Zhu, et al. Template-directed assembly of urchin-like CoS x / Co-MOF as an efficient bifunctional electrocatalyst for overall water and urea electrolysis[J], Inorg.Chem.Front., 2020, 7, 2602-2610) Co-MOF grown on nickel foam was obtained by a simple hydrothermal method, and then sodium sulfide was used as the raw material to obtain CoS x / Co-MOF nickel foam. In 1M KOH solution, the current density is 10mA·cm -2 Under the condition of , the overpotential is 280mV, and good stability is maintained after 1000 CV cycles and 10 hours of CP test. This technical solution prepares Co-MOF with high specific surface area on the surface of nickel foam in situ, and then reacts Co atoms into CoS through sulfurization. x As an active material. Although this technical solution achieves the technical effect of reducing overpotential, due to CoS x It comes from Co-MOF, so only some and a small amount of Co atoms on the surface of Co-MOF react. As a result, the content of active substances is relatively small, resulting in lower overall performance. At the same time, since the Co atoms in Co-MOF react to become active substances, the stability of the original organic framework is reduced, resulting in the collapse of the Co-MOF structure in the subsequent cycle process, resulting in reduced catalytic activity.
[0006] Based on the existing technology of similar principles mentioned above, for example, the previous work of the research group of the present invention, the existing document 3 (Du Maozhan, A ZIF-67 / NiCoMo-LDH composite material grown on nickel foam and its preparation method and application, 2024) first synthesized NiCoMo-LDH nanoflower balls loaded on NF by hydrothermal method, and then synthesized ZIF-67 loaded on NiCoMo-LDH nanoflower balls by hydrothermal reaction. It was used as a supercapacitor electrode material and tested, and charged and discharged in the voltage window range of 0-0.5V, and at a current density of 1-2mA cm -2 When the area specific capacitance is 2-4F cm -2 After stability testing, at a current density of 10 mA cm -2When the charge and discharge cycle is repeated for 10,000 times, 83% of the initial capacity is still retained. This technical solution is to synthesize NiCoMo-LDH nanoflowers with a high specific surface area in situ on nickel foam, wherein the metal Mo atoms and the Ni atoms and Co atoms form a synergistic effect to provide active sites; then grow ZIF-67 with a complete structure, which can protect the active sites of the original NiCoMo-LDH nanoflowers and improve stability. On the other hand, ZIF-67 itself has a high specific surface area and can also increase the active sites. However, the applicant's subsequent research found that since this technical solution grows ZIF-67 in situ on the surface of NiCoMo-LDH nanoflowers, ZIF-67 does not and cannot completely cover the NiCoMo-LDH nanoflowers, and therefore cannot provide a complete protective layer, thereby only slightly improving the stability of the NiCoMo-LDH nanoflowers.
[0007] In order to solve the above stability problem, a core-shell structure can be constructed, and the core layer material can be protected by the shell material as a protective layer, thereby improving the stability of the catalyst. For example, existing document 4 (Kang Ji, Xiao Zhang, Quande Che, et al. Composite nanoarchitectonics of ZIF-67 derived CoSe2 / rGO with superior charge transfer for oxygen evolution reaction [J], Electrochimica Acta, 2022, 426, 140785.) uses ZIF-67 synthesized by zeolite imidazolate and graphene oxide as precursors, sodium selenite is added thereto, and CoSe2 is generated on ZIF-67 by hydrothermal reaction, and then the graphene oxide is reduced to reduced graphene oxide to coat it. It was obtained in 1M KOH solution with a current density of 10mA cm -2Under the condition of , after 1500 CV cycles, the overpotential dropped by 34mV. The key technical feature of this technical solution is to coat MOF by introducing graphene, further protect and improve the integrity of the ZIF-67 structure, and isolate the contact between the electrolyte and ZIF-67, thereby increasing stability. However, the main problem with this technical solution is that in order to utilize and realize the induced growth effect of graphene oxide on the synthesis process of ZIF-67, this technical solution mixes graphene oxide with the raw materials of ZIF-67. The direct consequence of this operation is that when graphene oxide is subsequently reduced to reduced graphene oxide, a large amount of graphene is located inside the composite material, so the coating effect on the composite material is low, which is specifically reflected in its CV cycle test. After a long period of CV cycle, the stability of the catalyst is significantly attenuated; and there is also a problem with this technical solution. The contribution of reduced graphene oxide itself to reducing the overpotential is low, and the addition of graphene oxide will reduce the theoretical conductivity performance of the composite material.
[0008] In order to solve the above-mentioned problem of graphene coating effect, the preparation process can be adjusted, specifically, the order of adding raw materials can be adjusted to improve the coating effect and improve the stability of metal compounds with active sites. In the previous work of the research group of the present invention, the existing document 5 (Liu Meiling, a NF / rGO / Co-Ni-S / Mo-O self-supporting composite material and its preparation method and application, 2024) rGO was loaded on the surface of nickel foam by a water bath method, and then cobalt nitrate hexahydrate and nickel nitrate hexahydrate were added to obtain NF / rGO / Co-Ni-O through a hydrothermal reaction. Finally, ammonium molybdate tetrahydrate and thiourea were used as raw materials. After a hydrothermal reaction, NF / rGO / Co-Ni-S / Mo-O was obtained, and active substances MoO2 and CoNi2S4 were generated. Among them, MoO2 is coated on the surface of CoNi2S4 to form a core-shell structure. At a current density of 10mA·cm -2 , under the condition of a cycle time of 136h, the current retention rate is 98%. In this technical solution, only reduced graphene oxide is used as a surface modification material for modifying nickel foam. The key technology is to regulate the order of doping elements and react in steps. First, Co and Ni elements are doped to form a bimetallic oxide, and finally heteroatom S is introduced to sulfurize it to form CoNi2S4. At the same time, the metal Mo element forms a metal oxide MoO2, and MoO2 nanosheets grow evenly on the surface of CoNi2S4 to prepare a core-shell structure, which has better wrapping properties for the composite material. Because the two are bonded by chemical bonds, the force is significantly stronger than the van der Waals force of graphene coating, which is specifically reflected in the stability test. After a 136h cycle test, the current retention rate is 98%.
[0009] Although this technical solution can effectively improve the coating effect of graphene through the preparation process, it cannot fundamentally overcome the problem of reducing the theoretical overpotential. Therefore, in order to solve the coating problem without affecting the reduction of the theoretical overpotential, active materials that have the ability to reduce the overpotential can be used. A stable structure can be obtained through adjustment, and sufficient coating can be performed on the outside to protect the internal active materials and improve the stability. Summary of the invention
[0010] The purpose of the present invention is to provide a molybdenum-sulfur dual-doped cobalt metal organic framework and its preparation method and application. The existing technical problems are solved from the following aspects:
[0011] 1. In order to anchor more active sites, MOF materials with good pore structure and high specific surface area are used as substrate materials;
[0012] 2. In order to improve the conductivity of the catalyst, sulfur is introduced to accelerate the transmission of electrons on the catalyst surface;
[0013] 3. In order to improve the stability of the catalyst, a core-shell structure is constructed, and the strong binding force of the metal compound is used as a coating layer to provide protection and reduce the corrosion effect of the electrolyte;
[0014] The specific principle involved is: by doping S element on the MOF material with high specific surface area and adjustable pore structure, sulfide Co9S8 is formed on Co-MOF, changing the microstructure of Co-MOF; since Co9S8 has good electronic conductivity, it can improve the ion transport ability of the electrolyte in the material and improve the electrochemical performance of the composite material; at the same time, the surface of Co-MOF contains a large number of oxygen-containing functional groups, which can combine with the subsequently added Mo element to form a bimetallic oxide Co6MoO 12 Wrapped on the surface of the microspheres, it improves the stability of the catalyst through chemical bonding. In addition, molybdenum is a high-valent metal. After combining with Co atoms, it optimizes the electronic structure. The presence of Mo can change the electronic distribution and chemical properties of cobalt and improve the catalytic performance of Co atoms. Finally, Co9S8 / Co6MoO 12 They have a synergistic effect, further enhancing their original oxygen evolution catalytic activity.
[0015] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0016] A molybdenum-sulfur dual-doped cobalt metal organic framework is prepared by a solvothermal method using cobalt nitrate hexahydrate, trimesic acid, and thioacetamide as raw materials and N,N-dimethylformamide as an organic ligand to obtain a precursor of a sulfur-doped cobalt metal organic framework S-Co-MOF, wherein the main component is Co9S8; and then the precursor and ammonium molybdate tetrahydrate are used as raw materials and deionized water is used as a solvent to obtain a molybdenum-sulfur dual-doped cobalt metal organic framework Mo / S-Co-MOF by a hydrothermal method, wherein the main component is Co6MoO 12 ;
[0017] The microstructure of the S-Co-MOF is a microsphere structure composed of nanoparticles with a size of 10 μm; the microstructure of the Mo / S-Co-MOF is a microsphere structure with a rough surface and a size of 10 μm, wherein the Mo / S-Co-MOF has a core-shell structure, the core structure is composed of Co9S8, and the shell structure is composed of Co6MoO 12 constitute.
[0018] A method for preparing a molybdenum-sulfur dual-doped cobalt metal organic framework comprises the following steps:
[0019] Step 1, preparation of S-Co-MOF, first, under certain conditions, cobalt nitrate hexahydrate and trimesic acid are dissolved in N,N-dimethylformamide and stirred to obtain solution A, then, thioacetamide and urea are added to solution A in sequence, and stirring is continued to obtain solution B, and finally, under certain conditions, solution B is subjected to hydrothermal reaction, and the product obtained after the reaction is completed is washed, dried, and ground to obtain a sulfur-doped cobalt metal organic framework, referred to as S-Co-MOF;
[0020] In the step 1, the molar ratio of cobalt nitrate hexahydrate to trimesic acid is 1:1, and the mass ratio of thioacetamide to urea is 2:1;
[0021] In the step 1, the conditions for preparing solution A are: stirring time is 30-60 min at room temperature; the conditions for preparing solution B are: stirring time is 30-60 min;
[0022] In step 1, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 150° C. and the hydrothermal time is 12 h;
[0023] Step 2, preparation of Mo / S-Co-MOF, first, under certain conditions, dissolving ammonium molybdate tetrahydrate in deionized water and stirring to obtain a C solution, then adding the S-Co-MOF obtained in step 1 to the C solution, and continuing to stir to obtain a D solution, and finally, under certain conditions, subjecting the D solution to a hydrothermal reaction, washing, drying, and grinding the product obtained after the reaction to obtain a molybdenum-sulfur dual-doped cobalt metal organic framework, referred to as Mo / S-Co-MOF;
[0024] In the step 2, the mass ratio of ammonium molybdate tetrahydrate to S-Co-MOF is 2:1;
[0025] In step 2, the conditions for preparing solution C are: stirring time is 30-60 min at room temperature; the conditions for preparing solution D are: stirring time is 30-60 min;
[0026] In step 2, the conditions for the hydrothermal reaction are: the hydrothermal temperature is 100° C. and the hydrothermal time is 6 hours.
[0027] A molybdenum-sulfur dual-doped cobalt metal organic framework, when used as an oxygen evolution catalyst material, reacts in a 1M KOH solution and reacts at a current density of 10 mA cm in the range of 1 to 1.8 V. -2 When the overpotential is 255mV, the Tafel slope is 89mV·dec -1 ; After 48h of IT test, the current retention rate is 87-89%.
[0028] The technical effects of the present invention are shown by experimental tests:
[0029] The XRD and EDS tests of the present invention show that Mo / S-Co-MOF contains both Co9S8 and Co6MoO 12 The characteristic peaks of Mo / S-Co-MOF are obtained, and in addition to Co, S and O elements, there is also Mo element on the surface of Mo / S-Co-MOF, and the elements are evenly distributed. Comparing the test results with those of step 1, it can be seen that step 2 successfully removes the Mo element, that is, Mo / S-Co-MOF is successfully prepared.
[0030] The SEM test of the present invention shows that Mo / S-Co-MOF forms Co6MoO on the surface of S-Co-MOF microspheres. 12 Coating layer, and Co6MoO 12 Nanoparticles grow uniformly on the surface of Co9S8, i.e., core-shell structure, where the core structure is composed of Co9S8 and the shell structure is composed of Co6MoO 12 constitute.
[0031] The electrochemical performance test of the present invention shows that in 1M KOH solution, in the range of 1 to 1.8V, when the current density is 10mA·cm -2 When Mo / S-Co-MOF has an overpotential of 255 mV, the Tafel slope is 89 mV·dec -1 , after 48h of it test, the current retention rate was 87-89%.
[0032] Compared with the prior art, the present invention has the following advantages:
[0033] 1. The Mo / S-Co-MOF prepared by the present invention increases the pores and specific surface area by synthesizing Co-MOF and compounding with sulfur, thereby regulating and forming a regular porous microsphere structure, which helps to improve the ion transmission rate and solves the problem of low conductivity of Co-MOF;
[0034] 2. The present invention utilizes a large number of oxygen-containing functional groups on the surface of Co-MOF to form a bimetallic oxide with the Mo element. The two are combined with each other through chemical bonds to enhance the stability of the material;
[0035] 3. The Mo / S-Co-MOF prepared by the present invention has good electrocatalytic oxygen evolution performance. Co9S8 and Co6MoO 12 The active substances are interdependent, and the synergistic effect between different substances enhances their original oxygen evolution catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is the XRD test pattern of Example 1;
[0037] Figure 2 This is the SEM image of the S-Co-MOF prepared in Example 1;
[0038] Figure 3 It is the LSV curve diagram of Example 1 and Comparative Example 1;
[0039] Figure 4 It is the Tafel slope graph of Example 1 and Comparative Example 1;
[0040] Figure 5 This is the EDS image of Mo / S-Co-MOF prepared in Example 1;
[0041] Figure 6 This is the SEM image of Mo / S-Co-MOF prepared in Example 1;
[0042] Figure 7 It curve diagram of the Mo / S-Co-MOF sample prepared in Example 1;
[0043] Figure 8 It is the XRD test pattern of comparative example 1;
[0044] Fig. 9 This is the SEM image of Comparative Example 1. DETAILED DESCRIPTION
[0045] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0046] Example 1
[0047] A method for preparing a molybdenum-sulfur dual-doped cobalt metal organic framework comprises the following steps:
[0048] Step 1, preparation of S-Co-MOF, first, at room temperature, 0.582g of cobalt nitrate hexahydrate and 0.42g of trimesic acid were dissolved in 30mL of N,N-dimethylformamide, and stirred for 30min to obtain solution A, then, 0.1g of thioacetamide and 0.05g of urea were added to solution A in sequence, and the stirring was continued for 30min to obtain solution B, and finally, solution B was subjected to hydrothermal reaction at a hydrothermal temperature of 150°C and a solvent thermal time of 12h. After the reaction, the product was washed, dried and ground to obtain a sulfur-doped cobalt metal organic framework, referred to as S-Co-MOF;
[0049] In order to prove the composition of S-Co-MOF obtained in step 1, XRD test was performed. The test results are as follows Figure 1 As shown, S-Co-MOF has characteristic peaks of Co-MOF and Co9S8 at the same time. The test results show that step 1 successfully prepared Co-MOF, and compounded with S element, that is, successfully prepared S-Co-MOF.
[0050] In order to verify the microstructure of S-Co-MOF obtained in step 1, SEM test was performed. The test results are shown in Figure 2 As shown, the microscopic morphology of S-Co-MOF is a microspherical structure composed of nanoparticles with a size of 10 μm.
[0051] In order to demonstrate the electrochemical performance of the S-Co-MOF obtained in step 1, electrochemical performance tests were performed.
[0052] The specific method of the electrochemical performance test is to conduct the electrochemical performance test in a three-electrode system consisting of the material to be tested as the working electrode, the mercury oxide electrode as the reference electrode, the graphite rod electrode as the counter electrode, and 1M KOH solution as the electrolyte.
[0053] The specific preparation method of the working electrode is to mix 5 mg of S-Co-MOF powder catalyst with 295 μL of deionized water, 200 μL of anhydrous ethanol and 5 μL of Nafion binder, and then ultrasonicate for 30 minutes to obtain a dispersion; finally, drop the dispersion onto the nickel foam and dry it to obtain the working electrode. The nickel foam needs to be treated before use, and the treatment method is to wash the nickel foam with acetone, hydrochloric acid, deionized water and anhydrous ethanol in turn, and after washing, store it at a drying temperature of 60°C;
[0054] Test results such as Figure 3 As shown, in the range of 1 to 1.8 V, at a current density of 10 mA cm-2 When , the overpotential of S-Co-MOF is 286mV;
[0055] The Tafel slope is calculated by current polarization test. The test results are as follows Figure 4 As shown, the Tafel slope of S-Co-MOF is 97 mV·dec -1 .
[0056] Step 2, preparation of Mo / S-Co-MOF. First, at room temperature, 0.1 g of ammonium molybdate tetrahydrate was dissolved in 30 mL of deionized water, and the solution was stirred for 30 min to obtain a C solution. Then, 0.2 g of the S-Co-MOF obtained in step 1 was added to the C solution, and the solution was stirred for 30 min to obtain a D solution. Finally, the D solution was subjected to a hydrothermal reaction at a hydrothermal temperature of 100 ° C and a hydrothermal time of 6 h. After the reaction, the product was washed, dried, and ground to obtain a molybdenum-sulfur dual-doped cobalt metal organic framework, referred to as Mo / S-Co-MOF.
[0057] In order to prove the composition of Mo / S-Co-MOF obtained in step 2, EDS test and XRD test were performed.
[0058] EDS test results are as follows Figure 5 As shown, in addition to Co, S and O elements, there is also Mo element on the surface of Mo / S-Co-MOF, and the elements are evenly distributed;
[0059] XRD test results are as follows Figure 1 As shown, Mo / S-Co-MOF contains both Co9S8 and Co6MoO 12 The characteristic peaks of Co-MOF are absent. The reason is that the Mo element introduced in step 2 reacts with Co-MOF to form cobalt-molybdenum bimetallic oxide, namely Co6MoO 12 .
[0060] In order to verify the microstructure of Mo / S-Co-MOF obtained in step 2, SEM test was performed. The test results are shown in Figure 6 As shown in the figure, the microstructure of Mo / S-Co-MOF is a microsphere structure with a size of 10 μm and a rough surface. Compared with the S-Co-MOF obtained in step 1, it can be seen that after the reaction in step 2, the size of the microspheres has no obvious change, that is, the basic microstructure of the original Co-MOF can still be maintained. At the same time, a coating layer is formed on the surface of the original nanoparticles. Further combined with the XRD test results, it can be seen that the composition of the coating layer is Co6MoO 12 .
[0061] The above tests show that the Mo / S-Co-MOF obtained in step 2 has a core-shell structure, wherein the core structure is composed of Co9S8 and the shell structure is composed of Co6MoO 12 At the same time, the S element can still be detected in Mo / S-Co-MOF, which indicates that Co6MoO 12 The S-Co-MOF is not completely coated, that is, while a core-shell structure is formed, pores are still left. Combined with the existing common sense in the field, it can be known that this structure is beneficial to improving the electrochemical performance of the composite material.
[0062] The electrochemical performance test results of Mo / S-Co-MOF are shown in Figure 3 As shown, in the range of 1 to 1.8 V, at a current density of 10 mA cm -2 When the overpotential of Mo / S-Co-MOF is 255mV, compared with the S-Co-MOF obtained in step 1, it can be seen that the introduction of Mo element can significantly reduce the overpotential. The reason is that the Co6MoO formed in step 2 12 There is a synergistic effect between it and Co9S8.
[0063] The Tafel slope is calculated by current polarization test. The test results are as follows Figure 4 As shown, the Tafel slope of Mo / S-Co-MOF is 89 mV·dec -1 Compared with the S-Co-MOF obtained in step 1, the introduction of Mo element can significantly reduce the slope of Tafel. The reason is that the Co6MoO formed in step 2 12 / Co9S8 core-shell structure can accelerate the charge transfer rate.
[0064] In order to prove the stability of Mo / S-Co-MOF obtained in step 2, a stability performance test was performed. The test results are as follows Figure 7 As shown, the current density is 10 mA cm -2 , the current retention rate is 87% under the condition of a cycle time of 48h. The test results show that the Mo / S-Co-MOF composite material has good stability.
[0065] In order to demonstrate the effect of molybdenum-sulfur dual doping, Comparative Example 1 is provided, in which no molybdenum and sulfur are introduced, that is, Co-MOF prepared separately.
[0066] Comparative Example 1
[0067] A method for preparing Co-MOF, wherein the steps not particularly described in the specific steps are the same as the preparation method in Example 1, except that only step 1 needs to be performed, and no thioacetamide is added in step 1 to obtain a cobalt metal organic framework, and the obtained material is named Co-MOF.
[0068] In order to prove the composition of Co-MOF, XRD test was performed. The test results are shown in Figure 8 As shown, only the characteristic peaks of Co-MOF are present.
[0069] In order to verify the microstructure of Co-MOF, SEM test was performed. The test results are shown in Fig. 9 As shown, the microscopic morphology of Co-MOF is a spherical structure composed of nanorods with a size of 5 μm, wherein the nanorods are a disordered structure.
[0070] The electrochemical performance test results of Co-MOF are shown in Figure 3 As shown, in the range of 1 to 1.8 V, at a current density of 10 mA cm -2 When , the overpotential of Co-MOF is 295mV.
[0071] Compared with the S-Co-MOF obtained in step 1 of Example 1, it can be seen that doping with the S element can accelerate the transmission of electrons on the catalyst surface, that is, improve the conductivity;
[0072] Further comparison with the Mo / S-Co-MOF obtained in step 2 of Example 1 shows that the introduction of the high-valent element Mo can rearrange the electronic structure, induce lattice dislocation, and thus accelerate charge transfer; and the bimetallic Co6MoO 12 There is a synergistic effect with Co9S8 formed by introducing S element.
[0073] The Tafel slope is calculated by current polarization test. The test results are as follows Figure 4 As shown, the Tafel slope of Co-MOF is 121 mV·dec -1 .
[0074] Compared with the S-Co-MOF obtained in step 1 of Example 1, it can be seen that doping with the S element can not only directly increase the active sites, but also, after compounding with Co to form Co9S8, it can be activated when adsorbing oxygen ions, that is, activated oxygen ions are obtained, thereby reducing the energy barrier of the oxygen evolution reaction and accelerating the rate of the oxygen evolution reaction.
[0075] Further comparison with the Mo / S-Co-MOF obtained in step 2 of Example 1 shows that the Co6MoO 12 It can increase the active sites and at the same time, it has a synergistic effect with the core-shell structure formed between Co9S8 to accelerate charge transfer.
[0076] By comparing Example 1 with Comparative Example 1, it can be seen that the S element introduced during the synthesis of Co-MOF will react with the Co element to form Co9S8, providing sufficient active sites, and the Mo element is introduced to form Co6MoO 12, adjusting the valence state and electron density of Co, making it easier for the catalyst to react with the reactants. In addition, Co and Mo have a bimetallic synergistic effect, and Mo promotes the catalytic activity of Co atoms. Therefore, changing the electronic structure of the catalyst and improving the conductivity of the catalyst are helpful to enhance the electrochemical oxygen evolution performance.
[0077] In order to further demonstrate the effect of the practical application of the molybdenum-sulfur dual-doped cobalt metal organic framework, Comparative Example 2 is provided, using the commercial catalyst RuO2 for comparison.
[0078] Comparative Example 2
[0079] The working electrode was prepared using RuO2 as the active material for testing, which is referred to as RuO2 for short.
[0080] The electrochemical catalytic performance test results of RuO2 are as follows Figure 3 As shown, in the range of 1 to 1.8 V, at a current density of 10 mA cm -2 When , the overpotential of RuO2 is 323mV.
[0081] Compared with the Mo / S-Co-MOF catalyst obtained in step 2 of Example 1, it can be seen that the non-precious metal Co is used as the metal active center to synthesize Co-MOF. This is because the catalytic activity of Co element is poor, and S is doped to form Co9S8, which is different from Co6MoO formed by Mo doping. 12 These active substances can significantly increase the active sites of catalytic reactions and more effectively reduce the reaction overpotential.
[0082] The Tafel slope is calculated by current polarization test. The test results are as follows Figure 4 As shown, the Tafel slope of RuO2 is 111 mV·dec -1 .
[0083] Compared with the Mo / S-Co-MOF catalyst obtained in step 2 of Example 1, it can be seen that since the coordination ability of cobalt is relatively low compared with that of precious metals, it affects the interaction with the reactants and reduces the reaction rate. Therefore, new active sites are formed by doping Mo and S, Co6MoO 12 It has a synergistic effect with Co9S8, which can more effectively adsorb reactants and promote reactions, reducing the Tafel slope.
[0084] By comparing Example 1 with Comparative Example 2, it can be seen that the non-precious metal Co is used as the metal active center to synthesize Co-MOF, and the introduction of Mo and S improves the overall conductivity of the catalyst and promotes rapid electron transfer. 12 / Co9S8 core-shell structure, which has a synergistic effect and thus improves the catalytic performance.
Claims
1. A molybdenum-sulfur dual-doped cobalt metal organic framework, characterized in that: Using cobalt nitrate hexahydrate, trimesic acid, and thioacetamide as raw materials and N,N-dimethylformamide as organic ligand, a precursor S-Co-MOF with sulfur doping was obtained by solvothermal method, wherein the main component was Co9S8. Then, the precursor and ammonium molybdate tetrahydrate were used as raw materials, and deionized water was used as solvent to obtain a molybdenum-sulfur dual-doped cobalt metal organic framework Mo / S-Co-MOF by hydrothermal method, wherein the main component was Co6MoO 12 .
2. The molybdenum-sulfur dual-doped cobalt metal organic framework according to claim 1, characterized in that: The microstructure of the S-Co-MOF is a microsphere structure composed of nanoparticles with a size of 10 μm; the microstructure of the Mo / S-Co-MOF is a microsphere structure with a rough surface and a size of 10 μm, wherein the Mo / S-Co-MOF has a core-shell structure, the core structure is composed of Co9S8, and the shell structure is composed of Co6MoO 12 constitute.
3. A method for preparing a molybdenum-sulfur dual-doped cobalt metal organic framework, characterized in that The following steps are involved: Step 1, preparation of S-Co-MOF, first, under certain conditions, cobalt nitrate hexahydrate and trimesic acid are dissolved in N,N-dimethylformamide and stirred to obtain solution A, then, thioacetamide and urea are added to solution A in sequence, and stirring is continued to obtain solution B, and finally, under certain conditions, solution B is subjected to hydrothermal reaction, and the product obtained after the reaction is completed is washed, dried, and ground to obtain a sulfur-doped cobalt metal organic framework, referred to as S-Co-MOF; Step 2, preparation of Mo / S-Co-MOF, first, under certain conditions, dissolve ammonium molybdate tetrahydrate in deionized water and stir to obtain solution C, then add the S-Co-MOF obtained in step 1 to solution C, continue stirring to obtain solution D, finally, under certain conditions, subject solution D to a hydrothermal reaction, and after the reaction is completed, the product obtained is washed, dried, and ground to obtain a molybdenum-sulfur dual-doped cobalt metal organic framework, referred to as Mo / S-Co-MOF.
4. The preparation method according to claim 3, characterized in that: In the step 1, the molar ratio of cobalt nitrate hexahydrate to trimesic acid is 1:1, and the mass ratio of thioacetamide to urea is 2:1; In the step 2, the mass ratio of ammonium molybdate tetrahydrate to S-Co-MOF is 2:
1.
5. The preparation method according to claim 3, characterized in that: In the step 1, the conditions for preparing solution A are: stirring time is 30-60 min at room temperature; the conditions for preparing solution B are: stirring time is 30-60 min; In the step 1, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 150° C. and the hydrothermal time is 12 h.
6. The preparation method according to claim 3, characterized in that: In step 2, the conditions for preparing solution C are: stirring time is 30-60 min at room temperature; the conditions for preparing solution D are: stirring time is 30-60 min; In step 2, the conditions for the hydrothermal reaction are: the hydrothermal temperature is 100° C. and the hydrothermal time is 6 hours.
7. A molybdenum-sulfur dual-doped cobalt metal organic framework, characterized in that: When used as an oxygen evolution catalyst material, it reacts in 1M KOH solution and reacts at a current density of 10 mA cm in the range of 1 to 1.8 V. -2 When the overpotential is 255mV, the Tafel slope is 89mV·dec -1 .
8. A molybdenum-sulfur dual-doped cobalt metal organic framework, characterized in that: When used as an oxygen evolution catalyst material, after 48 hours of IT testing, the current retention rate is 87-89%.